CHARACTERISTICS AND ESSENCE OF DELINQUENS ADOLESCENT BEHAVIORS - Yu.S. Korovkina (Academy of Cognitive and Natural Sciences, 2022)
In given clause are considered essence delinquens behaviour, one of kinds deviations behaviour of the teenagers, the features and motives delinquention displays of the person of the teenager are opened.